The tst gene associated Staphylococcus aureus pathogenicity island facilitates its pathogenesis by promoting the secretion of inflammatory cytokines and inducing immune suppression. (January 2020) - Zheng, Yi; Qin, Chenhao; Zhang, Xianfeng; Zhu, Yifan; Li, Aiqing; Wang, Min; Tang, Yiwei; Kreiswirth, Barry N.; Chen, Liang; Zhang, Haifang; Du, Hong
Abstract: Staphylococcus aureus ( S. aureus ) is an important pathogen causing various limited or systemic infections. Methicillin resistant S. aureus (MRSA) in particular presents a major clinical and public health problem. Toxic shock syndrome toxin-1 (TSST-1) encoded by the gene tst is an important virulence factor of tst positive S. aureus, leading to multi-organ malfunction. However, the mechanism of TSST-1 in pathogenesis is only partly clear. In this study, we investigated the prevalence of the tst gene in clinical isolates of S. aureus . Then, animal experiments were performed to further evaluate the influence of the presence of the tst gene associated Staphylococcus aureus Pathogenicity Island (SaPI) on body weight, serum cytokine concentrations and the bacterial load in different organs. In addition, macrophages were used to analyze the secretion of cytokines in vitro and bacterial survival in the cytoplasm. Finally, pathological analysis was carried out to evaluate organ tissue impairment. The results demonstrated that the prevalence of tst gene was approximately 17.8% of the bacterial strains examined. BALB/c mice infected with tst gene associated SaPI positive isolates exhibited a severe loss of body weight and a high bacterial load in the liver, heart, kidney and spleen. Pathological analysis demonstrated that tissue impairment was more severe after infection with tst gene associated SaPI positive isolates. Moreover, the secretion of IL-6, IL-2 and IL17A by macrophages infected with tst gene associated SaPI positive isolates clearly increased. Notably, IL-6 secretion in BALB/c mice infected with tst gene associated SaPI positive isolates was higher than that in BALB/c mice infected with negative ones. Together, these results indicated that the tst gene associated SaPI may play a critical role in the pathological process of infection via a direct and persistent toxic function, and by promoting the secretion of inflammatory cytokines that indirectly induce immune suppression.